(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2026)
This article analyzes foreign and national experiences in developing financial literacy among students. It highlights the importance of financial literacy in the lives of young people, the necessity of forming this competency in higher education institutions, and effective approaches employed in the educational process. Based on foreign experiences, the advantages of organizing financial education through practical exercises, interactive methods, case studies, project work, and digital technologies are examined. Additionally, existing opportunities, challenges, and promising directions for improving students’ financial literacy within the national education system are analyzed.